The Chlamydia trachomatis Early Effector Tarp Outcompetes Fascin in Forming F-Actin Bundles In Vivo - Aranjuez, George F.; Kim, Jongeon; Jewett, Travis J. (Frontiers in Cellular and Infection Microbiology, 2022)
The intracellular pathogen Chlamydia trachomatis secretes multiple early effectors into the host cell to promote invasion. A key early effector during host cell entry, Tarp (translocated actin-recruiting phosphoprotein) is comprised of multiple protein domains known to have roles in cell signaling, G-actin nucleation and F-actin bundle formation. In vitro, the actin bundles generated by Tarp are uncharacteristically flexible, however, in vivo, the biological significance of Tarp-mediated actin bundles remains unknown. We hypothesize that Tarp’s ability to generate unique actin bundles, in part, facilitates chlamydial entry into epithelial cells. To study the in vivo interaction between Tarp and F-actin, we transgenically expressed Tarp in Drosophila melanogaster tissues. Tarp expressed in Drosophila is phosphorylated and forms F-actin-enriched aggregates in tissues. To gain insight into the significance of Tarp actin bundles in vivo, we utilized the well-characterized model system of mechanosensory bristle development in Drosophila melanogaster. Tarp expression in wild type flies produced curved bristles, indicating a perturbation in F-actin dynamics during bristle development. Two F-actin bundlers, Singed/Fascin and Forked/Espin, are important for normal bristle shape. Surprisingly, Tarp expression in the bristles displaced Singed/Fascin away from F-actin bundles. Tarp’s competitive behavior against Fascin during F-actin bundling was confirmed in vitro. Loss of either singed or forked in flies leads to highly deformed bristles. Strikingly, Tarp partially rescued the loss of singed, reducing the severity of the bristle morphology defect. This work provides in vivo confirmation of Tarp’s F-actin bundling activity and further uncovers a competitive behavior against the host bundler Singed/Fascin during bundle assembly. Also, we demonstrate the utility of Drosophila melanogaster as an in vivo cell biological platform to study bacterial effector function.